Akibat Hukum Terhadap Tuntutan Tanpa Kehadiran Terdakwa In Absentia (Studi Putusan Nomor 587/Pid.B/2019/Pn.Jkt.Pst) - Rosilda, Audy; Sunariyo, Sunariyo (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2025)
Indonesia, as a state of law based on Pancasila and the 1945 Constitution, is committed to upholding human rights and social justice for all its citizens. One of the major problems that threatens social order and public health is human organ trafficking. This research aims to explain the application of trial in absentia in the case of human organ trafficking in verdict No. 587/Pid.B/2019/PN.JKT.PST and its implications for criminal law enforcement. A normative juridical approach is used to reveal the fact that despite regulations prohibiting organ trafficking, this illegal practice continues to occur and is increasingly widespread.  The conclusion of this research is that although the trial in absentia in Decision Number 587/Pid.B/PN.JKT.PST provides a solution to the absence of the defendant, Ali Suryadi, who is undergoing palliative care due to cancer. The judge's decision to continue the trial despite the absence of one defendant reflects efficiency and commitment to law enforcement. However, this decision must be balanced with further evaluation of the sentence imposed, which needs to better reflect the deterrent effect and justice for victims. The implications of Decision Number 587/Pid.B/2019/PN.JKT.PST in criminal law enforcement related to human organ trafficking include humanitarian considerations that risk reducing the deterrent effect for perpetrators. The lenient sentence given to the defendant, albeit on health grounds, invites criticism because it does not reflect justice for victims. The sentence imposed must reflect justice for victims and provide a deterrent effect.